The Semiotics of Online Loans in the Representation Discourse of Women on Instagram @herstory.co.id - Puspitasari, Sendy Krisna; Arimbi, Diah Ariani; Srimulyani, Nunuk Endah (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
News coverage regarding illegal online loans (Pinjaman Online or Pinjol) targeting women is a frequent topic encountered on the Instagram social media platform. This study discusses the discourse of online loans in the news coverage presented by the Instagram account @herstory.co.id. The research focuses on analyzing: (1) how Instagram @herstory.co.id presents the representation of women within the text, and (2) describing the textual strategies used to feature women in the interpretation of online loans within the media coverage. This is a qualitative study utilizing the Sara Mills Discourse Analysis method. The research subject is the social media account Instagram @herstory.co.id, and the research object is women entangled in online loans. The findings indicate that Instagram @herstory.co.id has not yet prioritized women in its news texts. The news writers at @herstory.co.id tend to position women in the text as objects, and there is a tendency for the author to position themselves from the perspective of the dominant power. The strategy for featuring women in the interpretation of online loans in @herstory.co.id's coverage is executed in three ways: character, focalization, and schemata. Overall, the Instagram social media account @herstory.co.id still largely represents the image of women in accordance with general patriarchal culture.